A retrospective cohort study of the change in inflammatory parameters in childhood schizophrenia and bipolar disorder from childhood to adulthood: Neuroinflammation in schizophrenia and bipolar disorder - Sizer, Esra; Balca, Yeliz; Bulut, Mahmut; Çobanoğlu, Tuğba (Journal of Surgery and Medicine, 2022)
Background/Aim: The etiologies of childhood schizophrenia and bipolar disorder have not yet been clarified. In cases in which the symptoms of mood are not dominant and psychotic symptoms are more dominant, it may be difficult to distinguish between childhood schizophrenia and bipolar disorder diagnoses. Follow-up studies concerning this subject have indicated that approximately half of the adolescents diagnosed with bipolar disorder were first (and incorrectly) diagnosed with schizophrenia. Therefore, strong markers are still needed to be used in the differential diagnosis at the time of the first application. An increase in the number of studies on the neuroinflammatory process in pediatric schizophrenia and bipolar illness have started to appear in the literature. The neutrophil–lymphocyte, thrombocyte–lymphocyte, and thrombocyte–neutrophil ratio (NLR, TLR, and TNR, respectively) levels in patients with childhood schizophrenia and childhood bipolar disorder at the time of admission and five years later were evaluated to determine whether inflammatory markers changed over time. Methods: Twelve patients diagnosed with childhood schizophrenia and 14 patients diagnosed with childhood bipolar disorder were included in the study. Active infections, medical, neurological, endocrine, and metabolic illnesses, mental retardation, further concomitant psychiatric diagnoses, and intoxication were all exclusion factors. Hemograms from the same patients who satisfied the inclusion criteria when they originally applied and again at the fifth year follow-up were evaluated. Age, gender, neutrophil, lymphocyte, leukocyte, and thrombocyte values were recorded. NLR was calculated by dividing the neutrophil count by lymphocyte count. TLR value was calculated by dividing the thrombocyte count by lymphocyte count. TNR value was calculated by dividing the thrombocyte count by neutrophil count. Bipolar disorder and schizophrenia status were compared using NLR, TLR, and TNR parameters both at the time of initial diagnosis and at the fifth year of follow-up. Results: When the initial admission hemograms of patients with childhood schizophrenia or childhood bipolar disorder were examined, no statistically significant differences between the two groups in terms of NLR (P = 0.150) and TLR (P = 0.440) were found. TNR was significantly higher in childhood bipolar disorder patients than in childhood schizophrenia (P = 0.015). At the fifth year follow-up, the hemograms of individuals diagnosed with either childhood schizophrenia or childhood bipolar disorder were compared, and no statistically significant differences between the two groups in NLR, (P = 0.572),TLR (P = 0.758), and TNR (P = 0.328) were found. Conclusion: It was concluded that NLR and TLR levels did not change significantly over time in either disease and could not be used for the differential diagnosis of either disease. TNR may be considered for differential diagnoses in childhood schizophrenia and bipolar disease, particularly at the time of the first episode after confirmation of this study’s findings with future studies.